Developing and evaluating quality bilingual practices in higher education - Rubio-Alcalá, Fernando D.; Coyle, Do 1952- (Bilingual education & bilingualism, 2021)
This book provides an overview and evaluation of the quality of bilingual education found in internationalised higher education institutions. Its authors focus on the multifaceted roles that language(s) play in these growing multilingual spaces and analyse and identify the many factors that account for quality multilingual degree programmes